2023
DOI: 10.3389/fpls.2023.1065604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high night temperature on soybean yield and compositions

Abstract: IntroductionSoybean is sensitive to light and temperature. Under the background of global asymmetric climate warming.MethodsThe increase of night temperature may have an important impact on soybean yield. In this study, three varieties with different level of protein were planted under 18°C and 28°C night temperatures for investigating the effects of high night temperatures on soybean yield formation and the dynamic changes of non-structural carbohydrates (NSC) during the seed filling period (R5-R7).Results an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…The agronomic yield varies corresponding to physiological yield at changing regimes of day and night temperatures. Consistent with these studies, the current study reported a complete parallelism between the variation in physiological and biochemical traits below and beyond the optimum temperature T4 (35°C/27°C) (Figures 1-3), which was in accordance with the results of Alsajri et al (2019); Yang et al (2023), andChoi et al (2016). Additionally, the paired association of physiological, biochemical, and agronomic traits varies not only with changing regimes of temperatures but also with the nature of the cultivar used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The agronomic yield varies corresponding to physiological yield at changing regimes of day and night temperatures. Consistent with these studies, the current study reported a complete parallelism between the variation in physiological and biochemical traits below and beyond the optimum temperature T4 (35°C/27°C) (Figures 1-3), which was in accordance with the results of Alsajri et al (2019); Yang et al (2023), andChoi et al (2016). Additionally, the paired association of physiological, biochemical, and agronomic traits varies not only with changing regimes of temperatures but also with the nature of the cultivar used.…”
Section: Discussionsupporting
confidence: 90%
“…Although a rise in temperature impacts adversely the soybean reproductive phase and seed formation, the effect of temperature changes varies with extent, the period, and cultivars ( Djanaguiraman et al., 2019 ). It has been projected that soybean production decreased by 17% with every 1°C rise in temperature above optimum in soybean-growing regions ( Yang et al., 2023 ). In addition, the rise of temperature above optimum significantly decreases agronomic yield such as pods per plant, seed size, seed number, and seed yield in soybeans ( Choi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…While nighttime temperature may not be high enough to reduce pollen germination, it can still increase respiration rates, resulting in decreased grain biomass accumulation. This has been shown to occur in rice (Bahuguna et al, 2017) and soybean (Yang et al, 2023). Most models account for temperature effects on respiration, mainly via relationships between biomass and respiration rate.…”
Section: 4mentioning
confidence: 99%
“…Increased temperatures are also expected to increase efflux of carbon from soils because of increased respiration and reduction of soil water (Nissan et al., 2023). There is evidence (Cox et al., 2020) that nighttime temperatures are increasing faster than daytime, so the diurnal temperature differentials are higher and this differential can be more important than the temperatures themselves (Yang et al., 2023). While nighttime temperature may not be high enough to reduce pollen germination, it can still increase respiration rates, resulting in decreased grain biomass accumulation.…”
Section: Development Of Crop Modelsmentioning
confidence: 99%
“…This is attributed to the fact that minimum air temperatures modulate night‐time plant respiration rates, potentially reducing biomass accumulation and crop yields (Hatfield & Prueger, 2015; Kumudini et al, 2014; Sadok & Jagadish, 2020). For instance, night temperature plays an important role in soybean protein and oil accumulation, and high night temperatures result in a significant reduction in yield due to smaller seed size, lower seed weight and a reduced number of effective pods and seeds per plant (Song et al, 2016; Yang et al, 2023). Wheat, which is one of the leading agricultural products in the world, is most adversely affected by even short episodes of high night temperatures during the grain‐filling period, resulting in a significantly reduced yield (Mamrutha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%